Hubungan Alih Fungsi Lahan dan Perubahan Iklim terhadap Hasil Komoditas Pertanian di Jumantono - Ayu Prilyscia; Sutarno Sutarno; Rahayu Rahayu (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2018)
Land use conversion is a phenomenon of land use changes. The changes of land use and climate will affect on agricultural productivity. The purpose of this study was to analyze the changes of land use and climate that occurred in Jumantono District and the correlation between the land use conversion and the climate changes to agricultural productivity. This research was conducted in Jumantono District and Laboratory of Pedoogy and Climatology in Agriculture Faculty. Data be analyzed quantitavie descriptively and by correlation. The results showed that there was a change of land use area according to BPS in 2006-2007 and according to Google Earth Image analysis in 2004-2011 or 2011-2014 there ware changes of land use. Statistical analysis showed that land use changes and climate changes was significally correlated with land productivity.